Does context, practice or competition affect female athletes` achievement goal dominance, goal pursuit, burnout and motivation? - Fernandez-Rio, J.; Cecchini, J. A.; Mendez-Gimenez, A. (Journal of Human Kinetics, 2017)
The goal of this study was to assess the effects of two different achievement sport contexts, practice and competition, on the motivational profile of professional/semi-professional athletes. Forty-eight Spanish national/international-level female athletes (basketball = 18; handball = 12; soccer = 11; volleyball = 7), mean age 25.14 ± 3.43 years, agreed to participate in the study. They completed a questionnaire, prior and after training and competition, to assess achievement goals, achievement goal dominance, goal pursuit, motivational climate, motivation, burnout and perceived recovery-exertion. Data analyses revealed that, both in practice and competition, these team-sport athletes overwhelmingly showed a strong mastery-approach achievement goal in dominance as well as in pursuit. A significant finding was that this group of national/international-level, professional/semi-professional athletes not only adopted a mastery-approach achievement goal, but they also actively pursued it. It is also remarkable that this profile remained stable at post-tests, even after a painful defeat in competition, which produced a significant negative effect on the athletes` burnout (emotional and physical exhaustion and devaluation of sport participation) and self-determined motivation. As expected, the difference between total recovery and perceived exertion significantly increased after practice and competition. National/international-level team-sport professional/semi-professional female athletes held and pursue stable mastery-approach goal dominance.